Effect of high temperature drying on seed longevity of Bambara groundnut (Vigna subterranea) accessions - Jones, T.M.; Oyatomi, Olaniyi; Akinyele, B.O.; Odiyi, A.; Abberton, Michael T.; Hay, F.R. (International Seed Testing Association, 2020)
In this paper, we considered the effects of different drying regimes on the subsequent longevity of Bambara groundnut seeds. Freshly harvested Bambara groundnut seeds from 27 genebank accessions were divided into five samples. One sample (control) was immediately dried at 17°C/15% RH and the other samples were dried at 45°C/35% RH for up to eight days, before transfer to 17°C/15% RH. After drying, seed moisture content was raised to 10.9% before packing the seeds in aluminium foil packets and placing at 45°C. Samples were removed at regular intervals for germination tests to compare seed longevity. Initial drying at the higher temperature resulted in a faster reduction in seed moisture content. The effect of the different drying regimes on subsequent longevity was not significant for most accessions. Nonetheless, the seed longevity of smaller-seeded accessions was perhaps enhanced by initial drying at a higher temperature; in contrast, initial drying at 17°C appeared to be the best drying treatment for larger-seeded accessions. Overall, the results suggest that initial drying at a higher temperature was beneficial for reducing processing time and for some accessions would be beneficial for seed longevity, but further work is required to understand for which seed lots.